Manufacturing Transparent Soap from Tomato Juice (Solanum lycopersicum L.) as a Skin Moisture - Aliza, Ulfa; Yuniarti, Rafita (Pustaka Media Publishing, 2024)
Transparent soap is soap that has the highest level of transparency, capable of producing softer foam on the skin. Transparent soap is often referred to as glycerin soap, because in the process of making transparent soap, about 10-15% glycerin is added. The attractive appearance of transparent soap is luxurious and classy, causing transparent soap to be sold at a relatively higher price. Tomatoes are one of the best sources for lycopene production, lycopene has potential as an antioxidant and free radical scavenger so it is very beneficial for human skin health. The purpose of this study was to formulate a transparent soap from tomato juice as a skin protecting property and can moisturize the skin. The method used in this research is experimental method. Transparent soap formulation using tomato juice with a concentration of 20%, 30%, 40%. Evaluation of the transparent bath soap formulation includes organoleptic tests, water content, foam height, pH, irritation, humidity and hedonic preferences The results of the moisture test on the blank obtained a difference with a value of 0.66%, whereas in formula I there was a difference of 3.66%, in formula II there was a difference of 5.33%, and in formula III there was a difference of 8%. The results of the moisture test on the skin showed that the highest moisture was found in the formula with a concentration of 40%, there was a difference of 8%. Tomato essence transparent soap on the test for water content, foam height, and pH test has results that meet the requirements according to SNI (Indonesian National Standard). The conclusion from this study is that tomato juice can be formulated into transparent soap and meets SNI requirements.